Overexpression of BNIP3 in rat intervertebral disk cells triggers autophagy and apoptosis - Wu, Tingsheng; Fan, Shaoyong; Zhang, Bin; Tao, Zhiqiang; Hua, Hong; Dai, Min (Archives of Biological Sciences, 2022)
Paper description: Apoptosis of intervertebral disc cells is the primary cause of intervertebral disc degeneration (IDD). Bcl-2 and adenovirus E1B 19 kDa interacting protein 3 (BNIP3) is involved in cell autophagy and apoptosis. We explored the effect of BNIP3 on the autophagy and apoptosis in the isolated rat intervertebral disc cells by overexpression and RNA interference. BNIP3 overexpression in the rat intervertebral disc cells significantly upregulated the expression of the autophagy-related and pro-apoptotic proteins, the effects of which were substantially reversed by BNIP3 interference. BNIP3 enhanced autophagy and apoptosis of intervertebral disc cells in vitro, which might promote IDD development. Abstract: Excessive apoptosis of intervertebral disk cells and intervertebral disk degeneration (IDD) is the prime cause of low back pain. B-cell lymphoma 2 (Bcl-2) and adenovirus E1B 19 kDa interacting protein 3 (BNIP3), a member of the Bcl-2 family, are involved in cell autophagy and apoptosis. The roles and mechanisms of BNIP3 in intervertebral disk cell autophagy and apoptosis are unclear. In this study, primary rat intervertebral disk cells were prepared to study the effect of BNIP3 overexpression on their autophagy and apoptosis. The cell counting kit (CCK)-8 assay showed that BNIP3 overexpression decreased cell viability. Real-time PCR and Western blotting showed that BNIP3 overexpression significantly upregulated the expression of autophagy-related proteins and pro-apoptotic proteins, including hypoxia-inducible factor-1α, apoptotic protease activating factor 1, caspase 3 and cleaved caspase 3, microtubule-associated proteins 1A/1B light chain 3 (LC3) and Beclin-1 while downregulating the expression of anti-apoptotic protein Bcl-2. Cell staining detection of autophagy and apoptosis showed that BNIP3 overexpression increased the autophagy and apoptosis of rat intervertebral disk cells. BNIP3 RNA interference revealed that the effects of BNIP3 overexpression can be reversed. These findings suggested that BNIP3 enhanced the autophagy and apoptosis in the rat intervertebral disk cells in vitro, which might promote IDD development.